Tinjauan Yuridis Pelaksanaan Perjanjian Sewa-Menyewa Kapal Untuk Pengangkutan Batu Bara - Valentina Febriyanti; Ida Kurnia (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Gracious Code and the Commercial Code have given legitimate rules for the execution of rent understandings, particularly for the usage of transport rent assentions, but within the execution of this transport rent assention not everything went well. This is often since the activities of the parties included in this assention carry out their execution not in understanding with the assention that has been made. From activities that are not in agreement with the understanding that has been made, this may lead to default on the execution of the transport constitution assention. This investigate points to discover out the legitimate rules with respect to the usage of the dispatch rent understanding for the transportation of coal have satisfied or not satisfied and to discover out the reasons for defaults happening within the execution of the transport rent assention for the transportation of coal. The strategy utilized is regulating juridical with a statutory approach, utilizing essential information from appropriate directions and auxiliary information from pertinent lawful writing. Through subjective investigation, this investigate looks for to supply a more profound understanding of the lawful directions of the Gracious Code and the Commercial Code as a legitimate premise within the execution of transport constitution assentions which in their usage are frequently found to have defaults committed by the parties included within the constitution understanding. With this understanding, it is trusted that it can distinguish that the lawful rules with respect to this dispatch constitution agreement have been satisfied and give data with respect to the reasons why defaults can happen within the usage of the transport constitution understanding.